Mit Lewiatana w twórczości Andrieja Zwiagincewa (na materiale filmu „Lewiatan”) - Waligórska-Olejniczak, Beata (Studia Rossica Posnaniensia, 2016)
The article focuses on an interpretation of Andrei Zvyagintsev’s film Leviathan in the context of the Leviathan myth. The film was inspired by the Book of Job and the philosophical treatise called Leviathan or The Matter, Form and Power of a Common Wealth Ecclesiasticall and Civil written by Thomas Hobbes in 17th century. The article starts with an explanation of the possible meanings of the symbol of Leviathan in various cultural and historical traditions, including the Bible and Hobbes’s book. The background is then expanded further in the interpretation of selected shots from the film, which show that the artistic text of the Russian director can be perceived as a universal parable of human life.